Process for producing lithium metal and lithium alloy molded articles
By contacting the solution of metal lithium in ammonia with the deposition substrate under mild conditions, removing ammonia and deposition or alloying lithium, the problems of low energy density and high production process cost of existing lithium battery pack anode materials are solved, and efficient and low-cost lithium molded products are achieved.
Patent Information
- Application Number
- CN202180039842.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-06-04
- Filing Date
- 2021-06-03
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2041-06-03
AI Technical Summary
The anode material of existing lithium battery packs is mainly graphite, resulting in low energy density and high process cost and unsafe to produce thin lithium electrodes.
A low-cost process feasible and scalable under mild conditions, a molded product containing lithium is prepared by contacting a solution of metal lithium in ammonia with a metal or an electron-conductive deposition substrate, removing ammonia at a temperature of -100°C to 100°C, depositing or alloying lithium.
It realizes efficient production of pure metal lithium or lithium alloy molded products under mild conditions, reducing production costs, increasing energy density, and enhancing the safety of the battery pack.
Abstract
Description
[0001] The present invention relates to a process for producing lithium metal and lithium alloy moldings (bodies), in particular substrates coated or doped with metallic lithium for use as anodes in galvanic cells. Background Art
[0002] Solutions of alkali metals, in particular solutions of metallic lithium in liquid ammonia, have long been known (e.g., WC Johnson, MM Piskur, J. Phys. Chem. 37 (1933) 93-99). When such saturated solutions are cooled to <-60° C., phase separation occurs and a bronze-metal liquid layer with the composition Li(NH 3 ) 4 (so-called lithium bronze) is formed on the dilute blue solution (H. Jaffe, Z. Phys. 93, 1935, 741-761). The lithium / ammonia system is described in detail in R. Hoffmann et al., Angew. Chem. Int. Ed. 2009, 48, 8198-8232.
[0003] Solutions of alkali metals (e.g. lithium) in ammonia are metastable and thermally decompose according to the equation
[0004] 2M+2NH3→2MNH2+H2(M=Li, Na, K, Rb, Cs) (1)
[0005] The decomposition proceeds very slowly in the absence of water and oxygen. However, many transition metals (such as Fe 2+ ) catalyzes the decomposition reaction under the action of hydrogen evolution (Hollemann, Wiberg, "Lehrbuch der Anorganischen Chemie", 102nd edition, De Gruyter Verlag Berlin 2007, page 1296). From the study of the vapor pressure isotherms of compounds with the composition Li2(NH3)8 (dimeric lithium bronze), it can be inferred that in addition to the decomposition to the amide metal according to equation (1), there may also be a temperature-dependent dissociation equilibrium according to the following equation
[0006]
[0007] (F. Benoit, Bl. Soc. Chim. 33 (1923) 908-917).
[0008] US 4,206,191 A describes a process for preparing lithium amide, wherein a mixture of lithium metal, a liquid aromatic solvent (toluene), anhydrous liquid ammonia and a metal catalyst (finely divided metallic cobalt) is reacted at low temperature (0° C. to −60° C. or lower) to increase the rate of formation of the lithium amide compound while stirring to form a lithium amide solution, which is then converted into a finely divided dispersion of lithium amide in ammonia by raising the temperature to room temperature up to 60° C.
[0009] US 2008 / 0237538 A1 teaches how to prepare lithium bronze at temperatures below -33°C (the boiling point of NH3 at normal pressure) in the presence of an organic solvent (e.g. THF), and how to convert the lithium bronze into lithium amide in a subsequent step by thermal decomposition and hydrogen evolution in the presence of a hydrogen acceptor (1,3-diene or aryl olefin, such as styrene).
[0010] Furthermore, it is known that lithium bronze can be prepared by reacting lithium flakes in anhydrous ether at room temperature and obtained in pure form by phase separation using a separatory funnel (VIMel'nikova, KK Pivnitskii, J. Org. Chem. USSR (Engl. Transl.), 6, 2635, 1970).
[0011] EP 1 238 944 A1 describes the preparation of lithium bronze from a suspension of lithium particles and ammonia in hexane at room temperature (RT).
[0012] Finally, the formation of bronze from lithium wire and ammonia gas at room temperature in the absence of solvent has been reported (RH Müller, JG Gillick, J. Org. Chem. 43 (1978) 4647-8).
[0013] Currently commercially available lithium battery packs all function according to the intercalation principle. Graphite materials (corresponding to the formula LiC6) with a maximum capacity of 372 mAh / g are used as anodes. Higher capacities and thus higher energy densities can be achieved by partially or completely replacing graphite with alloy materials (e.g. silicon or tin, "alloy anode materials") or completely replacing graphite materials with metallic lithium.
[0014] Lithium metal has an extremely high electrochemical capacity of 3862 mAh / g. Since the capacity of common cathode materials is much lower (from only 150 to 300 mAh / g), this results in a very low specific area loading of <10 mAh / g for balanced battery cells (i.e. battery cells with a ratio N / P between negative and positive material close to 1). This corresponds to a lithium film thickness of 5 to 20 μm. However, current commercial films produced by extrusion and possibly then rolling processes can only achieve layer thicknesses of up to 50 μm, optimally 30 μm. When using 50 μm lithium foil, N / P ratios of 50 and above are provided. This unnecessarily high lithium input reduces the energy density (most of the lithium is not electrochemically used so far, so inactive "dead" material is formed). Furthermore, unnecessarily high metallic lithium input represents an avoidable cost factor and deteriorates the safety characteristics of such battery cells due to its high reactivity (J. Liu et al., Nature Energy 4, 180, 2019; P. Shi et al., Adv. Mater. Technol. 2020, 5, 1900806).
[0015] Therefore, to produce the thin lithium electrodes required for future lithium metal batteries, unfavorable and cost-intensive processes must be used, mainly PVD (plasma vapor deposition) technology, or processes operating at higher temperatures (such as melt deposition of lithium on the current collector at >180°C). Summary of the invention
[0016] The present invention aims to provide a low-cost process that is feasible and scalable under mild conditions for producing lithium metal-containing moldings (masters / stamps), such as moldings of lithium or lithium alloy foils. DETAILED DESCRIPTION
[0017] The process according to the invention is carried out in such a way that a 4+n A solution of metallic lithium in ammonia with n=0 to 10 is contacted with a metal or electronically conductive deposition substrate, and the ammonia is removed at a temperature of -100°C to 100°C by overflowing an inert gas or placing it under a pressure of 0.001 to 700 mbar, so that the remaining lithium is deposited on the deposition substrate or / and the deposition substrate is doped or alloyed with lithium.
[0018] The lithium metal and lithium alloy moldings (bodies / stamps) according to the invention are produced by thermal decomposition of a solution of pure metallic lithium in ammonia, preferably pure liquid lithium bronze (Li(NH3)4), in the absence of a transition metal-containing catalyst or hydrogen acceptor, at a temperature of up to 100°C, preferably up to 60°C, particularly preferably up to 40°C, and in contact with a deposition substrate. In the process, in contrast to the formation reaction, the ammonia is completely removed via the gas phase, so that elemental lithium metal remains, which is deposited on the surface of the device used and the deposition substrate positioned therein. In particular, the deposition substrate is a metal or an exclusively electronically conductive body in the form of, for example, a powder, granules, foil, sheet or a three-dimensional body with a hollow structure, for example a sponge. Lithium deposition can be purely physical (e.g. on metals that cannot be alloyed with lithium, such as copper, iron or nickel), but it can also reach the "inner volume" of the material by physicochemical means (e.g. in the case of sponge-like substrates or certain carbon materials, such as graphite, graphene, etc.) or otherwise involve alloy formation reactions (e.g. in the case of lithium-alloyable deposition substrates composed of silicon, germanium, tin, boron, aluminum, magnesium, antimony, etc.).
[0019] Surprisingly, it was found that, contrary to conventional wisdom, when the process conditions described in more detail below are observed, essentially no decomposition to lithium amide occurs, but rather pure metallic lithium is generated.
[0020] Since lithium bronze, having a Li:NH3 molar ratio of 1:4, contains the lowest ammonia content and therefore requires the least ammonia to be produced, said compound is an ideal starting material for the process according to the invention:
[0021] Li(NH3)4→Li o +4NH3↑ (3)
[0022] On the other hand, if a precipitate having the composition Li(NH3) is used 4+n In the case of a blue solution of lithium in ammonia, the superstoichiometric amount of ammonia (n molar equivalents) is first removed until the most concentrated liquid form of the lithium bronze is obtained. As the ammonia content increases, the efficiency of the process decreases and the amount of decomposition reaction to form undesirable lithium amide increases. For these reasons, in principle a dilute solution of lithium in liquid ammonia can be used, but for reasons of economic process, lithium bronze is preferably used.
[0023] The process is preferably carried out under reduced pressure, i.e. in the pressure range of 0.001 to 700 mbar. Alternatively, the ammonia can also be removed by passing an inert gas stream through the ammonia. Since the stripping gas reduces the concentration of the ammonia, the recovery of ammonia is more difficult, so the cost-effectiveness of the process is generally lower than that of a vacuum process.
[0024] The lithium source used is commercially available industrial lithium metal, or preferably, a purer battery or alloy grade. For example, such a metal grade can be obtained, for example, from Sigma-Aldrich-Fluka (SAF). For example, there is a 99% "high sodium" industrial grade with a maximum metal impurity of 15,000 ppm, of which the proportion of sodium is by far the highest. On the other hand, transition metals (especially Fe, Ag, Cu, Zn) are only present in the low ppm range (1-20 ppm). The sum of transition metal impurities is generally in the range of 100 ppm and below. In addition, SAF also provides battery quality lithium, i.e. a lithium content (based on metal trace elements) of 99.9%. This particularly pure battery quality contains up to 1500 ppm of other metal impurities, of which sodium also dominates in this case.
[0025] For the process according to the invention, metallic lithium is used with a cumulative transition metal impurity content of up to 200 ppm, preferably up to 100 ppm and particularly preferably up to 50 ppm. On the other hand, main group metals, in particular alkali metal and alkaline earth metal impurities, as well as boron and carbon group (Groups 13 and 14) impurities, in principle do not interfere with the process. Therefore, they can also be present in higher amounts, i.e. in amounts up to the percentage range.
[0026] A particular advantage of the process according to the invention is that even low-purity lithium metal grades with a correspondingly high content of transition metal elements can be used after a simple pretreatment. In this case, the thermally induced dissociation process is preceded by a simple filtration, centrifugation and / or decantation step. Since transition metals, especially iron, are largely insoluble in liquid ammonia and do not form ammonia compounds, they remain in solid form and can therefore be separated from the lithium ammonia solution or the lithium bronze by a solid / liquid separation step, respectively. The prepurification step can be carried out relative to the temperature over the entire liquid range of the lithium-ammonia solution used. In the case of lithium bronze, this is between -185°C and about 70°C. A temperature range between -40°C and 40°C is preferred. If a filter is used, the preferred pore size is a maximum of 10 μm, preferably a maximum of 2 μm and particularly preferably a maximum of 0.5 μm. Based on the lithium contained, the total (cumulative) content of transition metal elements in the purified lithium ammonia composition is a maximum of 200 ppm, preferably a maximum of 100 ppm and particularly preferably a maximum of 50 ppm.
[0027] The thermal decomposition or dissociation of lithium ammonia solutions and compounds, especially the defined lithium bronze, can occur in the presence of additional organic solvents (e.g. hydrocarbons, ethers or amines) or in the absence of such additives. Since the process heat released by the amide formation reaction can be dissipated more easily in the presence of a solvent that is inert or at least kinetically stable to lithium metal than in the absence of such additives, the presence of such a liquid solvent represents a preferred embodiment of the present invention. In particular, saturated hydrocarbons such as pentane, hexane, heptane, octane or common, commercially available mixtures of such compounds (industrial "petroleum ether", "white oil", "light gasoline") are suitable as solvents. Aromatic hydrocarbons can be used to a limited extent; aromatics are less preferred because they can promote undesirable decomposition and form lithium amide. Ether compounds such as diethyl ether, dibutyl ether, methyl tert-butyl ether, tetrahydrofuran, methyltetrahydrofuran, tetrahydropyran, glyme and the like can also be used, but are less preferred than the use of hydrocarbons. The reason for this is that lithium metal can react with ether compounds under adverse conditions and cleave the CO bond. This is a process that is only kinetically inhibited but highly exothermic. Accidents have been reported using lithium / THF systems on an industrial scale. Cyclic ethers are therefore in principle usable, but are particularly disadvantageous on an industrial scale. The volume of organic solvent that can be used to produce the defined lithium bronzes is between 20% and 500% of the volume of the lithium bronze.
[0028] Surprisingly, it has been found that the use of pure lithium (i.e. lithium metal having a total transition metal content of not more than 200 ppm, preferably not more than 100 ppm, particularly preferably not more than 50 ppm) suitably purified by solid / liquid separation or a lithium / ammonia solution or lithium bronze, followed by a thermal decomposition at mild temperatures above 100° C., preferably under reduced pressure, results in very pure, i.e. low-amino or non-amino lithium forms having an amide content of at most 1% by weight, preferably at most 0.1% by weight, relative to the total amount of deposited lithium.
[0029] Due to the high reactivity of metallic lithium and Li / NH3 mixtures, all process steps are carried out under an inert gas atmosphere (preferably argon, helium) or vacuum conditions.
[0030] The process according to the invention is particularly suitable for the direct production of thin lithium layers on conductor foils consisting of copper, iron, nickel or special carbon forms such as carbon nanotube foils (CNT foils, CNT = carbon nanotube) or graphene-based foils. Due to the poor lithium wettability of some commercial substrates, it may be necessary to pretreat them. The pretreatment includes, for example, the removal of any grease film that can be provided by washing with organic grease-soluble solvents, cleaning with washing active water or / and mechanical cleaning processes, such as grinding or polishing. In the case of copper, special lithiation processes, for example applying a defined oxide layer by thermal pretreatment under oxidizing conditions, as described, for example, in DE 10 2017 208 218 A1, provide the best results.
[0031] When a solution of lithium in liquid ammonia or especially lithium bronze is brought into contact with a metal substrate M capable of being alloyed with lithium, the corresponding alloy Li x M y Ammonia is unexpectedly formed and released under mild conditions. To form this alloy body, the desired metal M is added to the lithium bronze, preferably in the form of powder or particles. The added particles expand to form the alloy. After the ammonia is separated by distillation, a lithium-containing alloy material is obtained. Main group elements that can be alloyed with lithium, namely Be, Mg, Ca, Sr, Ba, B, Al, Ga, In, Si, Ge, Sn, Pb, Sb, Bi or any mixture thereof, are particularly suitable for the alloy formation process. It is also possible to use alloyable subgroup metals such as Zn, Ti or Zr, but it is sometimes difficult to avoid the formation of undesirable amides.
[0032] The alloy powder produced in this way can be applied to an electrical conductor foil by known purely mechanical pressing processes (calendering) or by means of a dispersed binder process (“slurry coating”) and thus processed into anode strips.
[0033] Metallic lithium freshly deposited from lithium-NH3 solutions in a vacuum or inert gas environment is very reactive towards air and moisture. In order to ensure its safety for further processing in technical applications, such as the construction of battery cells, passivation of the metal surface, i.e. the application of a thin protective layer, is a meaningful further processing step. Such processes involve contact with gaseous or liquid substances which form stable polymers and / or salts when in contact with lithium. Such processes are described, for example, in WO 2011 / 073324 A1.
[0034] The ammonia released during the ammonia dissociation can be liquefied in the plant and recycled, or preferably used directly in gaseous form to form new lithium bronze. Therefore, the ammonia can be recycled without an energetically disadvantageous liquefaction.
[0035] The lithium metal and lithium alloy mouldings are used to produce anodes for lithium batteries, for getter purposes or for chemically synthesized metal materials (preferably Li-Mg or Li-Al alloys).
[0036] The embodiments of the present invention will be summarized again below:
[0037] - A process in which the cumulative transition metal content of such a solution is only at most 200 ppm, based on the lithium contained.
[0038] - Processes in which the total (cumulative) transition metal content of this solution is only at most 100 ppm, based on the lithium contained.
[0039] - Processes in which the ammonia is removed at a temperature in the range of -20 to 80°C.
[0040] • A process in which the ammonia separation is carried out by adding an organic solvent selected from the group consisting of hydrocarbons, ethers or amines, the volume of the organic solvent being between 20% and 500% of the volume of the lithium bronze in the case of producing lithium bronze Li(NH3)4.
[0041] Processes in which the organic solvent is a saturated hydrocarbon.
[0042] Processes in which a metal or only electronically conductive body in a stamp such as a powder, granules, foil, sheet or a three-dimensional body with a cavity structure is used as a deposition substrate, the lithium deposition being carried out by a physicochemical process on a metal not alloyable with lithium, selected from the group consisting of copper, iron, nickel and / or as an alloy forming process in the case of a deposition substrate alloyable with lithium, selected from the group consisting of silicon, germanium, tin, lead, boron, aluminum, magnesium or antimony, or on a carbon-based material.
[0043] • Processes in which the carbon-based materials used are those based on carbon nanotubes or graphene.
[0044] • A process in which the lithium alloyable deposited substrate has a powder or granules of the alloying element with an average particle size ranging from 0.1 mm to 5 cm.
[0045] - A process in which a solution of lithium metal in ammonia is pre-cleaned by solid / liquid separation at a temperature of -185°C to 70°C, preferably in the temperature range of -40°C to 40°C.
[0046] • Processes in which filters with pore sizes in the range of 0.1 μm to 10 μm are used.
[0047] A process in which lithium bronze Li(NH3)4 is used.
[0048] · Process wherein the surface of the formed lithium coated or lithium alloyed body is passivated by a process carried out with a gaseous coating agent or a liquid coating agent, wherein the gaseous coating agent is selected from the group consisting of: N2, CO2, CO, O2, N2O, NO, NO2, HF, F2, PF3, PF5, POF3, and the liquid coating agent is selected from carbonates; chelated lithium borate solutions such as solutions dissolved in organic solvents, organic sulfur compounds, nitrogen-containing organic compounds, phosphoric acid, organic phosphorus-containing compounds, fluorine-containing organic compounds and fluorine-containing inorganic compounds, partially fluorinated hydrocarbons, BF3, LiPF6, LiBF4 or silicon-containing compounds.
[0049] - A process wherein the organic solvent is selected from the group consisting of oxygen-containing heterocycles, carbonates, nitriles, carboxylates or ketones, and the organic sulfur compound is selected from the group consisting of sulfites, sulfones, sultones.
[0050] • A process in which the metallic lithium coating on a collector foil consisting of Cu, Fe, Ni or a carbon-based material is produced as a lithium metal molding, the layer thickness of the applied lithium being in the range from 2 to 40 μm, preferably from 5 to 20 μm.
[0051] Example
[0052] Example 1: Production of lithium bronze from pure (transition metal-poor) lithium metal
[0053] In an inert (i.e., dry and filled with Ar) 1 / 2L double-jacketed glass reactor with a mechanical stirrer and a carbon dioxide snow cooler, 1.5g (215mmol) of lithium particles (particle size 3mm, sodium content = 0.45%, Fe = 26ppm; Zn = 2ppm, Cu = <10ppm) were placed in 200mL of industrial hexane at room temperature. Then, under sufficient stirring, 22L (920mmol) of ammonia gas were introduced within 3 hours. The reaction started after a few minutes and can be identified by the released solvation heat and the change of the lithium surface from silver to copper. The reaction heat was dissipated by jacket cooling so that the temperature of the reaction mixture was maintained in the range between 18 and 30°C.
[0054] After all the lithium has liquefied and converted to lithium bronze, the ammonia injection is terminated. The two liquid phases are separated by decantation and the upper light phase, lithium bronze, is filled into an inert glass bottle with a septum closure.
[0055] Yield: 15.8 g (98% of theoretical copper-colored liquid)
[0056] Example 2: Purification of lithium bronze
[0057] Lithium metal particles having an iron content of 210 ppm were used in a manner similar to that described in Example 1. After complete reaction with Li(NH3)4, the bronze was separated by decantation and filtered through a membrane filter with a pore size of 0.45 μm.
[0058] The filtered product had the following analytical results:
[0059] Li=13.2mmol / g
[0060] Fe = 2ppm, equivalent to 0.04μmol / g
[0061] This shows that the filtration step is able to remove 90% of the iron content introduced by the lithium raw material.
[0062] Example 3: Thermal dissociation of pure lithium bronze in vacuum
[0063] 3.63 g (48.4 mmol) of pure lithium bronze from Example 1 are added to an inert 50 mL glass Schlenk flask with a glass jacketed stirrer core. Under good stirring, the flask is evacuated using a diaphragm pump. The liquid begins to boil and splash. A silvery metallic film forms on the glass walls. Finally, after evacuation for 1 hour at 0.1 mbar, the vacuum is broken and replaced with argon. The mass of the non-evaporable residue is determined by weight difference measurement.
[0064] Result: 0.31 g (equivalent to 44.7 mol, calculated as lithium, 92% of the theoretical value)
[0065] Example 4: Deposition of lithium metal film on iron sheet
[0066] A stainless steel sheet measuring 2 x 4 x 0.3 cm was mechanically cleaned using fine sandpaper and degreased by rinsing first with acetone and then with hexane.
[0067] The flat sheet was then immersed in lithium bronze at normal ambient temperature for about 10 seconds. The sheet thus wetted was placed in a desiccator with exclusion of air and the ammonia was removed first at 500 mbar and then under full oil pump vacuum. In this way, an iron sheet partially coated with a thin silvery lithium film was obtained. Since the steel surface was not completely lithiated, some areas were not wetted by the lithium bronze and were therefore not coated with lithium.
[0068] Example 5: Production of lithium / aluminum alloy
[0069] In an inert 25 mL Schlenk flask with a glass-enclosed magnetic stirrer core were placed 2.9 g (39 mmol) of pure lithium bronze from Example 1 and cooled to 0° C. using an ice bath. 0.61 g of aluminum sand were then added and stirred for 1 hour at 0° C. Thereafter, the mixture was warmed to room temperature and the ammonia was removed in vacuo (finally at 0.02 mbar).
[0070] Yield: 0.86 g of silver-appearing alloy (98% of theory).
Claims
1. A process for producing lithium metal and lithium alloy molded products, characterized in that Make it have the composition Li(NH3) 4+n and a solution of metallic lithium in ammonia with n=0 to 10 is contacted with a metallic or electronically conductive deposition substrate and said ammonia is subsequently removed at a temperature in the range of -100°C to 100°C by flooding with an inert gas or placing under a pressure in the range of 0.001 to 700 mbar so that the remaining lithium (a) is deposited on said deposition substrate, (b) dopes said deposition substrate and / or (c) alloys said deposition substrate, wherein a metal or only electronically conductive body such as a powder, granules, foil, sheet or a three-dimensional body with a cavity structure in a stamp is used as a deposition substrate, in The deposition substrate on which the lithium deposition is carried out comprises one or more metals which are not alloyable with lithium and which are selected from copper, iron, nickel, or is carried out physically or physicochemically on a carbon-based material, and The lithium alloyed deposition substrate includes a lithium alloyable deposition material selected from the group consisting of silicon, germanium, tin, boron, aluminum, magnesium, and antimony.
2. The process according to claim 1, characterized in that The cumulative transition metal content of this solution is at most 200 ppm, based on the lithium contained.
3. The process according to claim 2, characterized in that The cumulative transition metal content of this solution is at most 100 ppm, based on the lithium contained.
4. The process according to claim 1, characterized in that The ammonia is removed at a temperature in the range of -20°C to 80°C.
5. The process according to claim 1, characterized in that The ammonia separation is performed by adding an organic solvent selected from the group consisting of hydrocarbons, ethers and amines, and in the case of preparing lithium bronze Li(NH3)4, the volume of the organic solvent is between 20% and 500% of the volume of the lithium bronze.
6. The process according to claim 5, characterized in that The organic solvent is a saturated hydrocarbon.
7. The process according to any one of claims 1 to 6, characterized in that The carbon-based material includes carbon nanotubes or graphene.
8. The process according to any one of claims 1 to 6, characterized in that The lithium alloyable deposition material is a powder or granules having an average particle size ranging from 0.1 mm to 5 cm.
9. The process according to any one of claims 1 to 6, characterized in that The pre-cleaning of the solution of lithium metal in ammonia is carried out by solid / liquid separation at a temperature in the range of -185°C to 70°C.
10. The process according to claim 9, characterized in that Filters with pore sizes ranging from 0.1 μm to 10 μm were used.
11. The process according to any one of claims 1 to 6, characterized in that Lithium bronze Li(NH3)4 is used.
12. The process according to any one of claims 1 to 6, characterized in that The surface passivation of the lithium-coated or lithium-alloyed molded articles is carried out by contacting them with a gaseous coating agent selected from the group consisting of N2, CO2, CO, O2, N2O, NO, NO2, HF, F2, PF3, PF5 and POF3, or a liquid coating agent selected from the group consisting of carbonates, solutions of chelated lithium borates dissolved in organic solvents, organic sulfur compounds, nitrogen-containing organic compounds, phosphoric acid, organic phosphorus-containing compounds, fluorine-containing organic compounds and fluorine-containing inorganic compounds and silicon-containing compounds.
13. The process according to any one of claims 1 to 6, characterized in that The surface passivation of the lithium-coated or lithium-alloyed molded articles is carried out by contacting them with a gaseous coating agent or a liquid coating agent, wherein the gaseous coating agent is selected from the group consisting of the following items: N2, CO2, CO, O2, N2O, NO, NO2, HF, F2, PF3, PF5 and POF3, and the liquid coating agent is selected from the group consisting of the following items: partially fluorinated hydrocarbons, BF3, LiPF6 and LiBF4.
14. The process according to claim 12, characterized in that The organic solvent is selected from the group consisting of oxygen-containing heterocycles, carbonates, nitriles, carboxylates, and ketones, and the organic sulfur compound is selected from the group consisting of sulfites, sulfones, and sultones.
15. The process according to any one of claims 1 to 6, characterized in that The metallic lithium coating on the collector foil, which consists of Cu, Fe, Ni or a carbon-based material, is produced as a lithium metal molding, wherein the layer thickness of the applied lithium is in the range from 2 to 40 μm.
Citation Information
Patent Citations
Method for producing an alkali metal-coated substrate by means of a binder layer and a binder layer and a coated substrate
DE102017208218A1
Process for the preparation of lithium amide
EP1238944A1
Process for Preparing Lithium Amide and a Composition Obtainable by Said Process
US20080237538A1
Preparation of lithium amide
US4206191A
Surface-passivated lithium metal and method for the production thereof
WO2011073324A1